Arthrodesis of Knee Joint With Compression Screws - RAO SAEED, FAISAL MUSHTAQ, YAWAR ANEES (Journal of Fatima Jinnah Medical University, 2018)
Twenty patients with tumors, trauma and paralytic conditions of the and knee joints were treated with the compression screws and arthrodesis was achieved at the knee joints . There were seven females and thirteen male patients. All the problems such as shortening, and angulation and deformity were addressed at the same time. We followed the radiological union and clinical observation to asess the achievement of union at the arthrodesis site.When all the 4 cortices were united on 2 orthognol views and patient were full weight bearing and mobile without support and pain, we accepted the success of the treatment. According to these criteria, we achieved excellent results in 18 (90%) cases of and failure in 1case (5%). One patient was lost from followup.Arthrodesis with compression screws is strongly recommended in achieving arthrodesis at the knee joint, especially in cases with severe posttraumatic arthritis in young age. It is less cumbersome and more tolerable in patients as compared to the external fixators. and costly intraarticular implants.This is an excellent method to deal with the young patients having severe post traumatic arthritis.